Insights on the In Vitro Wound Healing Effects of Sedum telephium L. Leaf Juice - Giorgio Cappellucci; Alessia Paganelli; Pier Luca Ceccarelli; Elisabetta Miraldi; Marco Biagi (Cosmetics, 2024)
Chronic wounds remain a significant clinical challenge, necessitating the exploration of novel therapeutic agents. Sedum telephium L. (syn. Hylotelephium telephium (L.) H. Ohba) fresh leaf juice, known for its traditional medicinal uses, was evaluated to assess its efficacy and its mechanism in promoting wound healing in vitro. Fresh leaves were collected and processed to obtain the juice, which was analyzed for polyphenols, flavonoids, polysaccharides, and proteins content. Key bioactive compounds were identified, including complex polysaccharides (2.47%), proteins (0.16%) and kaempferol and quercetin tri- di- and mono-glycosides, 0.04%, expressed as quercetin equivalent. The juice and its polysaccharidic fraction were tested on human keratinocytes (HaCaT) and fibroblasts (HFF-1) to assess cell viability, wound closure, and the production of growth factors and pro-collagen I. Our results indicated that the whole juice significantly enhanced wound closure in both cell types: +33% in keratinocytes compared to control, at 24 h, with a marked increase in fibroblast growth factor (FGF) (+21% compared to control) and LAP(TGF-β1) (+60% compared to control) and +30% in fibroblasts compared to control at 24 h, without a significant upregulation of pro-collagen I expression. The polysaccharidic fraction alone showed limited efficacy (no efficacy in keratinocytes and +20% in wound closure compared to control at 24 h in fibroblast), emphasizing the importance of the complete phytocomplex. These findings suggest that Sedum telephium L. represents a promising candidate in the setting of skin regeneration and repair.